Evaluation of the direct admission system in Kurdistan Regional Universities - Ahmed Tah Bilal (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
At the end of twentieth century and the beginning of twenty-one centuries, many aspects of the world have been changes, especially economy and marketing aspects. Consequently, the value of learning and education system has been increased, as well as education system has confronted many changes in different fields, for instance admission system for student and study programs has been change in order to be consistent with new circumstances. In addition, in the Iraq for the last fifty years “when ministry of high education is founded in Iraq (1970)” the central admission of high education system which depend only on student grades in the high school which is not appropriate because student may be accepted in the collage that is not compatible with their desire and ability. Furthermore, a relationship cannot be existed between students’ admission in universities and labour market demands. Likewise, “central admission” system has been used in Kurdistan region. It is an obvious that students’ grades may not represent really the desire and ability of students and it is not only appropriate measurement. Moreover, a very weak relationship between from high school and high education programs. However, in academic year (2017-2018) in government universities and instituted, new admission system which is “direct admission” has been applied by ministry of high education and scientific research in Kurdistan region. The main objective of this study is to evaluate the direct admission system that has been used in Kurdistan region universities in academic year (2017-2018), and help the responsible authorities by selecting the main positive and negative aspect of this system in order to make it better and an appropriate system for the future. Descriptive method has been used in this study by using questionaries’ for new admitted and previous students (second, third and fourth stages), direct interview with administration employees in Sulaimani university registration units, and the test questions that students should be take when apply for university have been checked and evaluated again. Moreover, current study identified some crucial conclusions for instance; variety of students (37.15%) chose their department compulsory, and only (29.71%) selected their department according to their desire and ability. Finally, majority of students indicate that direct admission system is better than previous one, but it needs improvements.